Understanding the effects of works councils on organizational performance: A theoretical model and results from initial case studies from the Netherlands - Jan Ekke Wigboldus; Jan Kees Looise; André Nijhof (Management Revue, 2008)
In this article, we present a conceptual model to understand the effects of works councils on organizational performance. The model is based on economic and HRM literature on employee participation and organizational performance, as well as on German and Dutch research into the economic and other effects of works councils. The model has been operationalized through a research approach and applied for the first time using in-depth case studies in a large insurance company in the Netherlands. In this paper we present the results of these case studies and the consequences for the model and the research approach. The findings show that works councils not only affect performance through changing employee attitudes and behavior - in a not dissimilar way to HRM - but also in a direct way by adding asymmetric information to the decision-making process and in an indirect way through influencing management attitudes and behavior. Thus the works council - performance relationship differs substantially from the HRM - performance relationship. The influence of the three potential mechanisms will depend to an extent on the characteristics of the works council and the organizational context. Further research is needed to determine how contextual conditions influence the positive effects of works councils on organizational performance.
Keywords: 650; works councils; organizational performance; the Netherlands